'One step up, but not there yet': using client feedback to optimise the therapeutic alliance in family therapy. Issue 1 (11th February 2020) - Rober, Peter; Van Tricht, Karine; Sundet, Rolf
Abstract : As research suggests that there is a strong link between the quality of the therapeutic alliance and the effectiveness of psychotherapy, family therapists should reflect on ways to improve the quality of the alliance. The systematic use of client feedback can be a rich resource as a response to the complexity of the alliance in the family therapy setting. In this paper the focus is on ways in which the client's systematic feedback can contribute to an optimisation of the therapeutic alliance. We present the Dialogical Feedback Tool (DFT), a simple feedback instrument to be used especially in family therapy sessions in which young children are involved. A case study illustrates how the feedback of clients on their experiences in therapy can help therapists to better attune to family members' experiences and expectations about therapy. Practitioner points: The therapeutic alliance in family therapy is complex, especially when children are involved Using a simple feedback instrument can help deal with the complexity of the therapeutic alliance The most important challenge for therapists using feedback instruments is how to integrate the feedback in a constructive way in the therapeutic process 抽象: "进了一步，但还没到"：使用来访者反馈优化家庭治疗中的治疗联盟 研究表明，治疗联盟的质量与心理治疗的有效性有着密切的联系，家庭治疗师应该思考如何提高联盟的质量。系统地使用来访者反馈可以作为应对家庭治疗情景中联盟的复杂性的一种丰富资源。本文的重点是如何使来访者的系统反馈有助于优化治疗联盟。我们介绍了对话式反馈工具（DFT），一种简单的反馈工具，适合特别是在有儿童参与的家庭治疗中使用。本文用一个案例研究说明了来访者对其治疗体验的反馈如何帮助治疗师更好地适应家庭成员对治疗的体验和期望。 对从业者的启示: 家庭治疗中的治疗联盟是复杂的，尤其是当儿童参与其中时 使用简单的反馈工具可以帮助处理治疗联盟的复杂性 对于使用反馈工具的治疗师来说，最大的挑战是如何在治疗过程中以建设性的方式整合反馈 Resumen: "Un paso adelante, pero todavía no": usar los comentarios de los clientes para optimizar la alianza terapéutica en terapia familiar Como la investigación sugiere que existe un fuerte vínculo entre la calidad de la alianza terapéutica y la efectividad de la psicoterapia, los terapeutas familiares deben reflexionar sobre las formas de mejorar la calidad de la alianza. El uso sistemático de los comentarios de los clientes puede ser un recurso rico como respuesta a la complejidad de la alianza en el entorno de la terapia familiar. Este artículo se centra en las formas en que la retroalimentación sistemática del cliente puede contribuir a una optimización de la alianza terapéutica. Presentamos la Herramienta de Retroalimentación Dialógica (DFT por sus siglas en inglés), un instrumento de retroalimentación simple que se utilizará especialmente en sesiones de terapia familiar en las que participan niños pequeños. Un estudio de caso ilustra cómo los comentarios de los clientes sobre sus experiencias en la terapia pueden ayudar a los terapeutas a sintonizarse mejor con las experiencias y expectativas de los miembros de la familia sobre la terapia. Puntos de implicación práctica: La alianza terapéutica en la terapia familiar es compleja, especialmente cuando los niños están involucrados. El uso de un instrumento de retroalimentación simple puede ayudar a lidiar con la complejidad de la alianza terapéutica. El desafío más importante para los terapeutas que utilizan instrumentos de retroalimentación es cómo integrar la retroalimentación de manera constructiva en el proceso terapéutico.